Pemeriksaan Bakteriologis Air Minum Isi Ulang Di Beberapa Depo Air Minum Isi Ulang Di Daerah Lenteng Agung dan Srengseng Sawah Jakarta Selatan - Radji, Maksum; Oktavia, Heria; Suryadi, Herman (Majalah Ilmu Kefarmasian, 2008)
Recently, refilled drinking water stores are flourishing in the some cities of Indonesia. This research tries to find out the quality of refilled drinking water at some shop in Jagakarsa, South Jakarta. The samples of refilled drinking water were taken from thir-teen shops around Lenteng Agung and Srengseng Sawah, Jagakarsa area. The bacte-riological test of refilled drinking water was to detect the availability of Coliform bacteria and identification of some bacterial pathogens such as Escherichia coli, Sal-monella, Staphylococcus aureus, Clostridium perfringens and Pseudomonas aeruginosa. It had been concluded that two of thirteen samples of refilled drinking water had the total number of bacteria above of the limit number according to the standard about the quality and requirement of drinking water. Four of the thirteen samples contain Sta-phylococcus aureus and none of the samples contain Escherichia coli, Salmonella, Clostridium perfringens and Pseudomonas aeruginosa.